Factors Controlling Bacterial Growth in Drinking Water Distribution Pipes - Lee, Yoonjin (Asian Journal of Chemistry, 2012)
In this research, the multiplication of total coliform and heterotrophic count was observed with the use of phosphate-based inhibitor on copper and poly(vinyl chloride) pipes. This result was confirmed with the outcomes of adenosine triphosphate testing. Heterotrophic count growth was limited by inorganic substances on copper and poly(vinyl chloride) in this test; the growth of heterotrophic count with the added condition of phosphorous was higher than that of carbon and efficiency of both organic and inorganic nutrients should be evaluated in the existing unit process in water plants. The scanning electron microscope result shows a depression dug out on the poly(vinyl chloride) pipe and deposits on the surface of pipe. Thermal disinfection might not be effective to control the growth of attached microorganism in the plumbing system.